Simvastatin inhibits 20-Hydroxyeicosatetraenoic acid formation: docking and in vitro assay - Yazun Jarrar; Mansour Almansour; Mansour Al-Sayed Ahmad; Belal O. Al-Najjar; Amin A. Al-Doaiss; Sireen Abdul Rahim Shilbayeh; Su-Jun Lee (BMC Pharmacology and Toxicology)
Abstract Introduction 20-Hydroxyeicosatetraenoic acid (20-HETE), a metabolite of arachidonic acid catalyzed mainly by cytochrome P450 (CYP) enzymes CYP4A11 and CYP4F2, plays a role in cardiovascular homeostasis. Elevated levels of 20-HETE are associated with hypertension. Accordingly, 20-HETE is a potential target for therapeutic interventions. Aims This study aimed to evaluate the effects of commonly prescribed statins simvastatin, atorvastatin, and rosuvastatin on 20-HETE formation in human liver microsomes and to conduct molecular docking simulations with CYP4A11 and CYP4F2. Methods Human liver microsomes were used to assess 20-HETE formation inhibition. Molecular docking simulations were performed using predicted structures of CYP4A11, CYP4F2, and CYP4F3B. The binding affinity of simvastatin was evaluated based on lowest energy of binding (LEB) values, and interactions with the heme group were analyzed. Results In vitro assay showed that simvastatin, but not other tested statins, inhibited the formation of 20-HETE in the human liver microsome with IC50 value of 10 µM and in a competitive mechanism as shown in the kinetics of the Lineweaver-Burk plot. Using in silico tools, simvastatin showed a significant inhibitory effect on CYP4A11, CYP4F2, and CYP4F3B with LEB values of -11.06, -9.93, and − 11.55 kcal/mol, respectively, indicating a stronger interaction compared to the known inhibitor HET0016. Simvastatin interacted predominantly with multiple hydrogen bonds and with the heme group of CYP4A11. Conclusions Simvastatin effectively inhibits the formation of 20-HETE most probably through interaction with CYP4A11, CYP4F2, and CYP4F3B, suggesting its potential as a therapeutic agent for managing conditions associated with elevated 20-HETE levels. Further clinical investigations are needed to explore its implications in cardiovascular diseases associated with elevated 20-HETE levels. Clinical trial number Not applicable.